2012
DOI: 10.2147/ijn.s38330
|View full text |Cite
|
Sign up to set email alerts
|

Design and application of chitosan microspheres as oral and nasal vaccine carriers: an updated review

Abstract: Chitosan, a natural biodegradable polymer, is of great interest in biomedical research due to its excellent properties including bioavailability, nontoxicity, high charge density, and mucoadhesivity, which creates immense potential for various pharmaceutical applications. It has gelling properties when it interacts with counterions such as sulfates or polyphosphates and when it crosslinks with glutaraldehyde. This characteristic facilitates its usefulness in the coating or entrapment of biochemicals, drugs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 124 publications
(180 reference statements)
0
21
0
Order By: Relevance
“…Chitosan has attractive properties for vaccine delivery applications, including high availability, biodegradability, and biocompatibility. In addition, high density of amino groups in chitosan allows facile chemical modification, complexation with negatively charged antigens, and muco-adhesiveness (59,60). Chitosan has been formulated into nano/microparticles without the use of organic solvents or high shear stress via ionotropic gelation and self-assembly of polyelectrolytes, preserving immunogenicity of antigens (61,62).…”
Section: Natural Polymer-based Particlesmentioning
confidence: 99%
“…Chitosan has attractive properties for vaccine delivery applications, including high availability, biodegradability, and biocompatibility. In addition, high density of amino groups in chitosan allows facile chemical modification, complexation with negatively charged antigens, and muco-adhesiveness (59,60). Chitosan has been formulated into nano/microparticles without the use of organic solvents or high shear stress via ionotropic gelation and self-assembly of polyelectrolytes, preserving immunogenicity of antigens (61,62).…”
Section: Natural Polymer-based Particlesmentioning
confidence: 99%
“…In searching for such delivery system, it is noticed that chitosan (CS), a cationic polysaccharide, has been widely used as a drug carrier due to its good biocompatibility and biodegradability and CS-based microsphere have shown some distinct advantages in delivery of various bio-active species ( 24 ). It has been demonstrated that CS-based microspheres as a drug delivery system (DDS) is able to reduce side effects, improve drug stability and enhance therapeutic efficacy of drugs and proteins ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chitosan (CTS) microsphere is a potential drug carrier and enhances absorption by opening tight junctions between the epithelial cells (Abdel Mouez et al, 2014). The CTS microsphere has been used as a promising carrier system for both vaccines and DNA (Islam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%